PENENTUAN POTENSI SEKTOR UNGGULAN DAN POTENSIAL DI PROVINSI MALUKU - Kharisma, Bayu; Hadiyanto, Ferry (Universitas Muhammadiyah Yogyakarta, 2018)
This paper aims to analyze the potentials of the leading sector and to formulate policy priorities for regional economic development in Maluku Province. The research methodology used in this research is Location Quotient (LQ), Growth Ratio Model (MRP) and Overlay analysis. The result of the research shows that in Maluku Province there are 8 economic categories that have basic sector namely agriculture, forestry and fishery category; categories of water supply, waste management and recycling; major trade-retail and auto-motorcycle repair categories; categories of transportation and warehousing; government administration, defense and compulsory social security schemes; categories of education services; categories of health services and social activities; and other service categories. The result of growth ratio (MRP) shows that the sector with the highest average regional growth rate (RPs) in Maluku province is mining and quarrying sector. Furthermore, overlay analysis shows that the sectors of government administration, defense, compulsory social security and large and retail trade; car and motorcycle repairs